(3GOGQI GdJShjb hGdefTBJ GdeYGUQIs - (3eUWai eMehO(B, (3GHh HcQs ((3GdGScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2004)
(3gPG GdcJGH jJfGhd GdMbGFb GdJj jZadgG GdHYV Yf egfI GdJShjb hPdc ef NdGd GdaUhd GdJGdjI eONd GSJQGJjLj JWHjbj aj GOGQI GdJShjb aj GdefTBJ GdeYGUQI, GdGSS hGdbhGYO GdegfjI dfTGW GdJShjb hGdHjY, LhgQ hfWGb hXjaI GdJShjb hGdHjY, bQGQ GdYecjd HGdTQGA hCQcGf hXjaI GdJShjb hGdHjY OQGSI GdHjFI hGdJNWjW GdGSJQGJjLj dhXjaI GdJShjb hGdHjY, JShjb GdNOGeJ HGdJWHjb YGi fTGW GdSjGMI , GdHjY GdTNUj hEOGQI GaQGO GdHjY GdTNUj , hXjaI GdJShjb hGdJLGQI GdGdcJQhfjI YHQ GdGfJQfJ, bjGS hJbjje caGAI haYGdjI fTGW GdJShjb hGdHjYs
Keywords: (3GOGQI GdeHjYGJs; (3GdJShjbs